Corrigendum to “Water Quality Assessment for Irrigation Water Use in Lake Hazar Basin, Elazığ, Turkey” [Türk Tarım ve Doğa Bilimleri Dergisi 7(1): 231–247, 2020] - Çeliker, Murat; Parlakyıldız, Nurettin; Öztürk, Mualla (Mevlüt AKÇURA, 2020)
The author wishes to notify a small change as follows. The original Table 2 had a miscalculation, it should be replaced with the correct one as the following: The author would like to apologize to the readers if any inconvenience this may have caused.

The author wishes to notify a small change as follows. The original Table 2 had a miscalculation, it should be replaced with the correct one as the following: The author would like to apologize to the readers if any inconvenience this may have caused.
Corrigendum to “Water Quality Assessment for Irrigation Water Use in Lake Hazar Basin